Key Design Points of the Reserved Rail Transit Project in Xiong’an New Area Underground Integrated Transportation Hub - LI Heyong; XING Jiayong; MAO Wei (Chengshi guidao jiaotong yanjiu)
［Objective］ In view of the inconsistency in the construction schedule of the large underground integrated transportation hub in Xiong’an New Area, it is necessary to conduct in-depth research on the key design points of the reserved rail transit projects in the construction of above-mentioned transportation hub, in order to reduce the impact of secondary construction and lower the difficulties, risks and investments in later stages. ［Method］ The basic profiles of hubs such as Xiong’an Intercity Station, Xiaoli Station and Financial Island Station in Xiong’an New Area are introduced. The necessity of reserving rail transit projects in underground integrated transportation hub is analyzed. The design concepts for the above projects are summarized, and their key design points are extracted. ［Result & Conclusion］ Key design points for the reserved rail transit project in the transportation hub are as follows: The system types and vehicle formations shall be determined based on the planning conditions; Reasonable station locations and station types shall be decided with the idea of overall optimization; Station and city integration shall be used as a strategy to coordinate urban and traffic functions；The layout plan of the hub shall be improved with the concept of integrated design; Following the principle of intensive and appropriate development, the phased construction of the hub shall be studied; The reserved and pre-embedded measures shall be coordinated for detailed implementation.